2021
DOI: 10.1186/s12913-021-06959-3
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire survey investigation of the present status of dietetic consultation at community pharmacies from the perspectives of registered dietitians and pharmacists

Abstract: Background Registered dietitians are rarely employed at community pharmacies in Japan, even though dietetic advice might benefit some patients. Objective To clarify the present status of dietetic consultation provided by registered dietitians and their collaboration with pharmacists in community pharmacies. Methods We conducted a cross-sectional questionnaire-based survey of pharmacists and registered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…An education that includes the above fields allows for the systematic development of skills from the higher levels of Bloom’s Taxonomy [ 40 ] as students are not only aware of the presence of other health professions (remember), but also have the opportunity to familiarise themselves with their competencies and identify challenges that require collaboration (understand), implement protocols of practice (apply), draw conclusions on the relevance of cooperation (analyze), discuss the advantages and disadvantages of implemented solutions (evaluate), and propose innovative solutions to patient care based on the skills and knowledge of all team members (create). One of the examples of the collaboration between postgraduate dietitians and pharmacists regarding remember and understand levels of Bloom’s taxonomy is the study by Kizaki et al [ 41 ]., in which pharmacists and dietitians were asked to rate their feelings about the availability of dietary advice in pharmacies in Japan. When surveyed, 70% of pharmacists found this type of service useful.…”
Section: Discussionmentioning
confidence: 99%
“…An education that includes the above fields allows for the systematic development of skills from the higher levels of Bloom’s Taxonomy [ 40 ] as students are not only aware of the presence of other health professions (remember), but also have the opportunity to familiarise themselves with their competencies and identify challenges that require collaboration (understand), implement protocols of practice (apply), draw conclusions on the relevance of cooperation (analyze), discuss the advantages and disadvantages of implemented solutions (evaluate), and propose innovative solutions to patient care based on the skills and knowledge of all team members (create). One of the examples of the collaboration between postgraduate dietitians and pharmacists regarding remember and understand levels of Bloom’s taxonomy is the study by Kizaki et al [ 41 ]., in which pharmacists and dietitians were asked to rate their feelings about the availability of dietary advice in pharmacies in Japan. When surveyed, 70% of pharmacists found this type of service useful.…”
Section: Discussionmentioning
confidence: 99%
“…According to the US Bureau of Labor Statistics, dietitians and nutritionists “plan and conduct food service or nutritional programs to help people lead healthy lives.” ( Kizaki et al, 2021 ) Similarly, the Association of UK Dietitians describes the professional activities of dietitians as interpreting nutrition science “ to improve health and treat diseases/conditions by educating and giving practical, personalised advice to clients, patients, carers and colleagues.” ( US Bureau of Labor Statistics. Dietitians and Nutritionists.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published survey among pharmacists and nutrition specialist found that `pharmacists acknowledged the need of nutritional and dietary care in community pharmacies and hoped that certified dietitians would be significantly involved. 10 Therefore, early introduction of this topic through IPE sessions is crucial to limit the problem in clinical practice and to enhance collaboration among healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%